Les relations de genre en Asie centrale protohistorique : redéfinition et discussion - Élise Luneau (Les Nouvelles de l’Archéologie, 2015)
The study of the funeral practices of the Oxus civilization − a sedentary agro-pastoral and proto-state society located in southern Central Asia and dated from the Bronze Age (2400-1500 BCE) − allowed the particular social structure related to gender of this society to be shed in light. Female graves may contain more funeral gifts and more artefacts in precious material. In addition, a preferential distribution of the funeral goods in relation with the sex of the individuals and the type of graves could be observed. Some objects are nearly exclusively associated to women, whereas others to men. A connection between the types of funeral goods and the sex of the individuals appears obvious, although some variations look like normative conflicts, which remains to be interpreted. Nevertheless, the goods put in the graves could have acted as attributes of gender or of functions.The precise examination of the material culture and the iconography associated to each sex question the assertions previously raised concerning the social roles and status of the individuals in relation with the gender. It contributes to review our positions on the social activities, the status of women and men, and their relation, as well as to redefine the roles and powers of each one. The analysis allows thus the social organization of the Oxus civilization to be considered in a new way, particularly the gender system, which seems to be based more on an equality of status and a complementarity of powers and functions between men and women.